INCREASED UNDERSTANDING OF IPS MATERIAL ON EVENTS SURROUNDING THE PROCLAMATION OF INDEPENDENCE WITH MINDMAPPING MEDIA IN CLASS V - Banowati, Sekar Mayang; Rosyid, Ainur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
The lack of social studies learning comprehension among class V pupils at SD Negeri Kedoya Utara 03 served as the impetus for this study. The purpose of this study is to improve fifth-graders' comprehension of social subjects via mediamindmapping at SD Negeri Kedoya Utara 03. Collaboration-based classroom action research was used to conduct this study. This study was conducted in two cycles, with planning, implementation, observation, and observation comprising each cycle. Fifth-graders at SD Negeri Kedoya Utara 03 served as the study's subjects. This study focused on how well pupils understood social studies. procedures for gathering data that involve testing, observation, and documenting. Both qualitative descriptive analysis and quantitative descriptive analysis are employed as data analysis methodologies. The study's findings demonstrate how media usemindmapping might enhance class V students' comprehension at SD Negeri Kedoya Utara 03. This accomplishment was proven after two rounds of action. Cycle I students understood 69.28% of the social studies material, whereas cycle II students understood 87.67%. Another achievement was the evaluation of student activities, which in cycle I achieved 67.70% and increased to 85.39% in cycle II. The instructor activity score increased from cycle I's 67.72% to 82.68%.